Kombinasi Shibori dan Batik Serta Motif Bunga Tulip Dengan Teknik Embellishment Pada Ready to Wear Deluxe - Seftiani, Selvia; Suharno, Suharno; Marlianti, Mira (Jurnal Pendidikan dan Penciptaan Seni, 2025)
The creation of this ready-to-wear deluxe is based on empirical facts, that a ready-to-wear deluxe collection that harmoniously combines elements of Japanese culture (shibori), Indonesian cultural heritage (batik), and visual representation of iconic Dutch plants (tulips) does not yet exist. Therefore, this creative research aims to present innovation in ready to wear deluxe by exploring the synergistic potential of the three elements above through embellishment techniques. The urgency is that in addition to being a medium for cultural diplomacy through fashion, this research can enrich the treasury of fashion design with a unique global perspective, while preserving and applying traditional techniques in a contemporary context. The creative method used is the Double Diamond Model, which includes the stages of discover, define, develop, and deliver. The result of this creative research is the creation of four ready-to-wear deluxe collections that are innovative and relevant to the current luxury fashion market. This collection was presented at the 2024 Indonesia International Muslim Fashion Festival (IN2MF) event at the Jakarta Convention Center..